2021
DOI: 10.1149/2162-8777/ac2079
|View full text |Cite
|
Sign up to set email alerts
|

Performance Improvement of Sb Phase Change Thin Film by Y Doping

Abstract: Yttrium-doped Sb phase change thin films were prepared by magnetron sputtering and the in-situ resistance temperature measurement system was used to study the process of phase change thin films. With the addition of yttrium atoms, the crystallization temperature of Sb thin film increases, indicating improvement of their thermal stability and data retention ability. Furthermore, yttrium-doped Sb thin films have higher crystalline and amorphous resistance, which is conducive to the phase transition by Joule heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, the Y-doped In 3 SbTe 2 (IST) material has a fast and stable phase transition rate because the Y substitution for In results in a large amount of lattice distortion and negative doping formation energy in the lattice structure [15]. Our previous research has observed that Y-doped Sb and Y-doped Ge 1 Sb 9 materials are more stable at high temperatures and have smaller grains [16,17]. However, few studies on yttriumdoped Sn 15 Sb 85 materials have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Y-doped In 3 SbTe 2 (IST) material has a fast and stable phase transition rate because the Y substitution for In results in a large amount of lattice distortion and negative doping formation energy in the lattice structure [15]. Our previous research has observed that Y-doped Sb and Y-doped Ge 1 Sb 9 materials are more stable at high temperatures and have smaller grains [16,17]. However, few studies on yttriumdoped Sn 15 Sb 85 materials have been reported so far.…”
Section: Introductionmentioning
confidence: 99%